Occurrence state of co-existing arsenate and nickel ions at the ferrihydrite-water interface: Mechanisms of surface complexation and surface precipitation via ATR-IR spectroscopy. (September 2018) - Wang, Chao; Cui, Yong; Zhang, Jinghai; Gomez, Mario; Wang, Shaofeng; Jia, Yongfeng
Abstract: Arsenic and nickel are common contaminants that usually co-exist in many contaminated natural and mining environments. More research on the interaction of these two contaminants is needed such as their coordination structure and occurrence state at mineral-water interfaces. In this study, we investigated the structure of surface complexes and surface precipitates formed by co-existing As(V) and Ni(II) ions at the ferrihydrite-water interface by varying the order of adsorption processes, pH, aging time and Ni(II) concentration using attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR). ATR-FTIR analysis revealed the presence of complexed AsONi bonds which produced ternary surface complexes. These ternary AsONi surface complexes formed through a layer by layer alternative coordination on top of the binary AsOFe surface site complexes of ferrihydrite. Such multilayer surface complexes formed as initial surface precipitates which were found to refine their surface structure from amorphous to crystalline phases and were a function of incubation time, coverage of multilayer surface complexes, Ni(II) concentration and pH. Our results presented here can well explain the formation process of surface precipitates on the molecular scale and are of use to forecast the fate and mobility of commonly As(V) and Ni(II) species at the ferrihydrite-water interface commonly found in natural or mine tailings water-soil environments. Highlights: Ternary surface complexes formed by AsONi bonds on the surface of ferrihydrite. Surface precipitation including adsorption, polymer formation, crystal formation. Time, coverage, concentration, pH are key factors in surface precipitate evolution.